Divine Narratives in Xenophon’s Anabasis - Haywood, Jan (Histos, 2016)
This paper builds on recent work that has focused on the interplay between Xenophon the narrator and Xenophon the character in the Anabasis. It illustrates how crucial the divine is in the construction of Xenophon’s character and the overall shape of the narrative. By referring to oracles, dreams and sacrifices, as well as his divine estate at Scillus, Xenophon the narrator contributes substantively towards wider thematic concerns in the narrative: the meaningful role of the divine in warfare; Xenophon’s stellar record during this opaque foreign campaign, and the signal connection between piety and good leadership.